Factors Influencing Burnout of Registered Nurses University Hospitals in the Northeast during the Epidemic Situation of the COVID-19 - Sookpier, Pornpimon; Srijakkot, Jitpinan; Dapha, Sompratthana; Suwunnung, Pornpit (Executive Journal, 2023)
This study has two primary objectives: 1) To investigate the burnout experienced by registered nurses in a university hospital in the northeast during covid-19 epidemic, and 2) To examine the factors influencing burnout among registered nursed in the same university hospital during the covid-19 epidemic. In this research, data collection was conducted through the use of questionnaires. The sample comprised 140 registered nurses from a university hospital in the northeast, selected via stratified random sampling. The statistical analyses employed included frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The study yielded the following outcomes: 1) The overall level of burnout among registered nurses in a university hospital in the northeast during the covid-19 epidemic was assessed as low. 2) Among the factors influencing burnout in registered nurses at the same hospital, workload perception ranked the highest, followed by operational environmental factors. These two factors accounted for 33.20% of the variability, with a forecasting error of ±0.346.